Luaran Terapi Balloon Eustachian Tuboplasty pada Disfungsi Tuba Eustachius - Ida Ayu I. Larassanthi; Yully Prapyatiningsih (Universitas Sam Ratulangi, 2023)
Abstract: Eustachian tube dysfunction (ETD) is a common condition complained by patients and most of them are still managed today by medical therapy. Newer management techniques such as Balloon Eustachian Tuboplasty (BET) has been introduced. This study aimed to evaluate the available studies regarding the indications, safety, and efficacy of BET in reducing the symptoms of patients with ETD. This was a systematic review study. A comprehensive literature search was carried out according to PRISMA guidelines, and seven articles were obtained. The follow-up results showed a significant improvement in the ETDQ-7 score and the results of middle ear assessments. Progress observed over 1-12 months confirmed the efficacy and demonstrated the durability of the BET procedure, without complications that occurred during follow-up. In conclusion, based on the literature review the procedure BET was found to be safe and efficient in the short and long terms up to five years post operatively in patient with chronic ETD. Keywords: Balloon Eustachian Tuboplasty; Eustachian tube dysfunction Abstrak: Disfungsi tuba Eustachius (ETD) merupakan kondisi yang umum dikeluhkan oleh pasien dan sebagian besar masih dikelola saat ini dengan terapi medis. Dewasa ini teknik manajemen yang lebih baru seperti Balloon Eustachian Tuboplasty (BET) telah diperkenalkan. Penelitian ini bertujuan untuk mengevaluasi studi-studi yang tersedia mengenai indikasi, keamanan, keberhasilan BET dalam mengurangi gejala pasien ETD. Jenis penelitian ialah suatu systematic review. Pencarian literatur dilakukan secara komprehensif sesuai dengan pedoman PRISMA. Hasil penelitian mendapatkan tujuh artikel untuk dilakukan tinjauan sistematis. Hasil follow-up dari semua peserta yang menjalani BET menunjukkan peningkatan bermakna berdasar-kan skor ETDQ-7 dan hasil penilaian telinga tengah. Perkembangan selama 1-12 bulan menunjuk-kan kemanjuran dan daya tahan prosedur BET tanpa disertai komplikasi berat yang muncul selama masa follow-up. Simpulan penelitian ini ialah prosedur BET dilaporkan aman dan efektif dalam jangka pendek dan jangka panjang hingga mencapai lima tahun pasca operasi pada pasien dengan ETD kronis. Kata kunci: Balloon Eustachian Tuboplasty; disfungsi tuba Eustachius